Tingkat Pengetahuan Masyarakat terhadap Terapi Komplementer Akupuntur pada Masyarakat di Desa Pematang Kuyung, Kelumbayan, Tanggamus - Sugiarto Sugiarto; Arina Asrofulmawa; Meli Nurhidayah; Seli Oktaviana; Masidah Masidah; Yulia Reviana; Vike Mutiara Sani; Anggun Nuraini; Elda Santika; Rahmi Nabilah; Heru Sunandar; Irshad Irtiza Husain (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Acupuncture complementary therapy is a form of non-conventional treatment that is widely sought after by the public to improve health and reduce pain complaints. This study aims to determine the level of public trust in acupuncture complementary therapy and the factors that influence it. The research method used a quantitative descriptive approach with a questionnaire distributed to 20 respondents as a data collection technique. The questionnaire included an assessment of public knowledge of acupuncture therapy. The analysis results showed that 68% of respondents had a high level of trust in acupuncture therapy, 24% had moderate trust, and 8% had low trust. The conclusion of this study is that the majority of the public has high trust in acupuncture therapy as a complementary effort to improve health after receiving education about acupuncture complementary therapy.